Motivational Management in Agricultural Enterprises - Demydova, Marija; Демидова, Марія Миколаївна (Non-governmental organization «Eurasian Social Sciences Association», 2017)
In this scientific article the main factors of stimulation of motivation of the personnel of agrarian enterprises in the control system are considered and determined. The algorithm of stages of the motivational mechanism of the personnel of the agro enterprise is presented. У цій науковій статті розглядаються та визначаються основні фактори стимуляції мотивації персоналу аграрних підприємств. Представлено алгоритм етапів мотиваційного механізму персоналу підприємств агропромислового комплексу.
Мотиваційний менеджмент в агропідприємствах
In this scientific article the main factors of stimulation of motivation of the personnel of agrarian enterprises in the control system are considered and determined. The algorithm of stages of the motivational mechanism of the personnel of the agro enterprise is presented. The necessity of introducing the considered motivation algorithm in order to obtain the corresponding results is indicated. It is emphasized that the effectiveness of the motivation is manifested through the productive work of the employees involved in the production process. The organizational mechanism of forming the motivation model for the personnel of agrarian enterprises is offered. У цій науковій статті розглядаються та визначаються основні фактори стимуляції мотивації персоналу аграрних підприємств. Представлено алгоритм етапів мотиваційного механізму персоналу підприємств агропромислового комплексу. Вказано на необхідність введення розглянутого алгоритму мотивації для отримання відповідних результатів. Підкреслюється, що ефективність мотивації проявляється через продуктивну роботу працівників, що беруть участь у виробничому процесі. Запропоновано модель мотивації персоналу аграрних підприємств.
Keywords: motivation; мотивація; agro enterprise; аграрні підприємства; personnel; персонал; stimulation; стимуляція; efficiency; ефективність